Circular Pedagogy to Support Technological Universities Cultural Transformation - Ivaylo Peev; Jon-Hans Coetzer; Nadia Barkoczi; Iulia Stefan; Todor Todorov; Patrick Flynn; Claudia Marian; Sonia Munteanu; Lia Pop; Lucia Morales (Irish Journal of Academic Practice)
European countries need active and proactive educational systems assisted by models that can drive a cultural transformation, which supports sustainable socio-economic and environmental development. In this paper, we reflect on the future of European education by engaging on a critical review of the literature, which informs the further development of a novel pedagogy that we have coined as “Circular Pedagogy.” We offer some insights on how the foundations of a new educational model (ANEM) could be cemented and solidly supported by pillars that acknowledge our societies' rich and diverse cultures. Furthermore, the discussions are framed as part of the European University of Technology's (EUt+) consortium, as we reflect on its future educational model. Technological universities are in need of novel pedagogies that drive change as we “think human first.” European education faces significant challenges derived from the need to enable learning environments guided by equity, diversity, and inclusive frameworks for all categories of diverse learners. We propose a learner-centred, dynamic, and proactive pedagogy that can help us to manage and navigate the inevitable cultural conflict that will emerge as different societies and individuals seek to work together, to enable a better understanding and identification of the triggers that might arise due to potential cultural clashes and detachment.